Effect of metal-fingers/doped-ZnO transparent electrode on performance of GaN/InGaN solar cell. (September 2017) - Routray, S. R.; Lenka, T. R.
Abstract: The effect of doped-ZnO transparent conductive oxide (TCO) with metal (Ag)-fingers contact on GaN/InGaN solar cell is investigated through numerical simulations. An optical and electrical analysis of different dopant elements (such as B, Al, Ga, In and Sn) with ZnO as a top TCO layer is studied. A comparative analysis of metal square pad electrode, metal grid pattern electrode and metal-finger/ZnO type electrodes are taken into consideration to ensure the effect of anti-reflectivity by ZnO. The effect of thickness of ZnO and i-InGaN layer on performance of solar cell is also studied in detail. The proposed solar cell structure with Ag-fingers/ZnO:Al as top contact electrode shows interesting device characteristics compared to other dopants and metal top electrodes. The device achieves open circuit voltage ∼2.525 V, short circuit current ∼4.256 mA/cm 2, fill factor ∼87.86% and efficiency ∼9.22% under 1 Sun, air mass 1.5 global illumination.